Ranger Himung: Mitigating Youth Delinquency Through Increasing Legal Resilience with Spoken Media (Madihin) - Utami, Suci; Tajmila, Tajmila; Hafizah, Noor; Rahman, Muhammad Abdi; Alroy, Davin (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
Juvenile delinquency in the city of Banjarmasin is an increasingly worrying social phenomenon, especially with the emergence of trends such as the use of addictive substances and motorcycle gang violence. This trend illustrates the need for immediate intervention to prevent further escalation and maintain the safety of the school environment. Legal awareness education in schools is considered the right strategy to build positive character in adolescents, reduce deviant behavior, and strengthen their legal resilience. This community service study was carried out at SMPN 3 Banjarmasin by applying a socio-legal juridical approach in the form of a serial workshop. This program consists of four series that focus on the formation of harmonious, inclusive, independent, and superior characters through legal counselling delivered in the context of Madihin, a traditional art of South Kalimantan. Spoken Media is an interactive approach used to integrate local cultural values in learning, including the values of tolerance, non-violence, and gender equality. Program evaluation is carried out through pre-tests and post-tests using questionnaires to measure the improvement of student's legal knowledge, understanding, attitudes, and behavior